Anteseden dari Brand Loyalty pada Brand Smartphone di Indonesia - Novita Romadhowati (Jurnal Ilmiah Wahana Pendidikan, 2023)
The study looked at the relationships between perceived quality, brand trust, and knowledge, as well as between perceived quality, brand trust, knowledge, customer satisfaction, also brand loyalty. This study, "purposive sampling" utilized as a sample strategy, and the respondents had to be owners of smartphones from Samsung, Apple, Vivo, Oppo, or Xiaomi. 264 individuals completed questionnaires that provided the core data for this research. According to the study's findings, perceived quality positively affects brand trust, brand trust favorably affects brand knowledge, perceived quality favorably affects brand knowledge, brand trust favorably affects brand knowledge, and brand knowledge favorably affects brand loyalty.